The Comparative Analysis of the Characteristics and Psychological Structures of Sociability, Self-Discipline and Responsibility of StudentsFuture Managers and Specialists in the Field of People Management - A G Aleykin (Peoples' Friendship University of Russia (RUDN University), 2011)
The article presents the results of the comparative analysis of systematic study of sociability, self-discipline and responsibility of students-future managers and specialists in the field of people management: similarities and differences in the manifestation of the conceptual-semantic and instrumental-stylistic characteristics, as well as correlation and factor structures.